2021
DOI: 10.1016/j.socscimed.2021.113798
|View full text |Cite
|
Sign up to set email alerts
|

Parental unemployment during the Great Recession and childhood adiposity

Abstract: The incidence of adiposity in the early years of life has outgrown the prevalence rate in older children and adolescents globally; however, the relationships between unemployment and weight are predominantly studied in adults. This study examines the relationship between changing economic conditions during the Irish recession and child weight. Fixed effect logistic regression is used to examine the effects of parental unemployment on weight using the Growing up in Ireland infant cohort from 2008 to 2013. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…A before‐after‐crisis approach revealed that overweight in Spanish children below the age of 15 increased 8.5% from 2006 to 2010/2012 (Rajmil et al, 2013). A study carried on in young Irish children between 2008 and 2013, found that the probability of a child being classified as overweight/obese was 8% higher if either parent experienced unemployment (Briody, 2021). County‐level unemployment in 2008–2012 was also found to be associated with increased obesity risk in the United States (Oddo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A before‐after‐crisis approach revealed that overweight in Spanish children below the age of 15 increased 8.5% from 2006 to 2010/2012 (Rajmil et al, 2013). A study carried on in young Irish children between 2008 and 2013, found that the probability of a child being classified as overweight/obese was 8% higher if either parent experienced unemployment (Briody, 2021). County‐level unemployment in 2008–2012 was also found to be associated with increased obesity risk in the United States (Oddo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The number of families who could afford to pay for extracurricular and sport activities decreased with the economic crisis (Briody, 2021; González‐Bueno et al, 2012; Verde‐Diego et al, 2020). Low PA is commonly connected with screen overuse, and both phenomena increased among Greek children during the years throughout the Great Recession (Venetsanou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies found that adverse economic conditions could harm the physical and mental health of children under 18 due to disruption of normal family processes, restricted access to health services, reduction in well-being investments, personal unhappiness, family tension, stressful situations, conflicts between parents, and antisocial behaviours (Briody 2021;Aleman-Diaz et al 2016;Elgar et al 2015;World Health Organization 2012;Harper and Jones 2011;Carlo et al 2011;Conger et al 2010;Solantaus et al 2004). Rajmil et al (2014) provided an international study concerning the impact of the 2008 economic crisis on children's health.…”
Section: International Experiencesmentioning
confidence: 99%